School inclusion of autistic student in a public school of São Paulo State - M. D. Oliveira; T. V. Souza; G. C. F. Donati (Scientific Electronic Archives, 2017)
This study aimed to analyze the mode how the inclusion of students with Global Development Disorders has been in a State School of the Public Education Network. The motivation of this research was the constant complaint of teachers to work with the students of Special Education, specifically the student with autism spectrum Disorder. After analysis it was concluded that among the study participants teachers there is a great desire to acquire specific training and availability of technology to better conduct their educational activities